Epidemiological tracking and control strategies of early mortalities in hatchery-reared gilthead seabream (Sparus aurata) larvae - Alaa Eldin Eissa; Rabia El Ziltne; Asmaa Edrees; Asmaa O. El-Ramlawy; Mahmoud S. Sharaf; Reda Korany; Hany M. R. Abdel-Latif; Ibrahim Hassan Ibrahim; Abeer E. Mahmoud; Rehab Qorany; Shimaa Mansour; Sarah A. A. Ibrahim; et al. (Aquaculture International, 2025)
Implementing competent biosecurity strategies is a key factor for maintaining a disease-free aquaculture. Bacterial infections are an eminent threat to all live stages occurring in the marine hatchery. Live foods, including algae, rotifers, and artemia, are potential sources of microbial infections in hatcheries with ineffectual biosecurity plans. In the present study, epidemiological, bacteriological, molecular, and histopathological investigations were carried out on all critical live components of the marine hatchery, including batches of algal cultures, rotifers ( Brachionus plicatilis ), artemia ( Artemia salina ), eggs, cultured gilthead seabream ( Sparus aurata ) larvae, and other inanimate components such as water supply. Clinically, fish larvae had pale skin and exhibited sluggish and frequent erratic swimming patterns. Two Vibrio isolates were presumptively identified by using the API 20E system. After molecular screening and phylogenetic analysis, these isolates were confirmed to be V. alginolyticus and V. vulnificus . Remarkably, V. alginolyticus was the most commonly recovered species from seawater, eggs, algae, rotifers, and artemia cultures. Both of these Vibrio isolates exhibited diverse sensitivities to different antibiotics used in the antibiogram, with maximal susceptibility to florfenicol. Therapeutic and preventive programs were imposed at different rearing stages after tracing the potential sources of infection.

Nutritional modulation using Nigella sativa with or without feed restriction as a novel strategy to boost growth and immunity and combat edwardsiellosis in Oreochromis niloticus - Asmaa S. A. Abdel-Daim; Nema S. Shaban; Olfat Shehata; Mervat A. Abdel-Latif; Mohamed S. Sobh; Asmaa Edrees (Aquaculture International, 2025)
Medicinal plants occupy a privileged place and are considered one of the most important natural phytogenic feed additives. Black cumin ( Nigella sativa , NS) and its derivatives have several beneficial therapeutic properties for aquaculture farms. This study investigated the effects of NS with or without feed restriction on growth performance, haemato-biochemical profile, immune and oxidant/antioxidant status, as well as the resistance of Oreochromis niloticus ( O. niloticus ) to Edwardsiella tarda ( E. tarda ) challenge. A total of 360 fish with initial body weight (mean ± SE) 26.68 ± 0.08 g were randomly distributed into four groups with nine replicates (10 fish each) as follows: ad libitum control (Ad C), ad libitum Nigella sativa (Ad NS), restricted control (Res C), and restricted Nigella sativa (Res NS). The O. niloticus in the first (Ad C) and third groups (Res C) were fed with the basal control diet without NS supplementation. The second (Ad NS) and fourth (Res NS) groups were fed on diets supplemented with 3% NS. The fish in the Ad C and Ad NS groups were fed ad libitum during the experimental period, while the Res C and Res NS groups were subjected to 2 days of feed restriction weekly (third and seventh days of the week). At the end of the feeding trial (2 months), the experimental groups were combated against edwardsiellosis by intraperitoneally injection of 0.1 mL (1 × 10 5 CFU) E. tarda. The survival of the fish was evaluated for a further 7 days. The results revealed that growth metrics of fish were substantially higher in the Ad NS group, followed by the Ad C and Res NS groups. The feed conversion ratio (FCR) was substantially lower in the feed-restricted groups compared to the ad libitum groups. Biochemical analysis showed a significant decrease in hepatic enzymes as well as glucose levels in all experimental groups compared to Ad C. Moreover, total cholesterol and LDL-c were reduced ( P ) in both Nigella groups. The growth hormone and leptin were higher in all groups, particularly Res NS group compared to the Ad C group however, cortisol level significantly reduced in the Res NS group only compared to the control group. There were substantial elevations in lysozyme and IgM in all groups, particularly the Res NS group. Also, the oxidant/antioxidant status had been improved mostly in the Res NS group. Histopathological examination revealed that combining NS with feed restriction maintained normal histology in the intestine, liver, kidney, and spleen. Furthermore, the combined treatment significantly reduced mortality rates following challenges with E. tarda , highlighting a potential protective role. In conclusion, dietary intervention of 3% NS with or without feed restriction can enhance fish productivity, immunity, organ function, and disease resistance. Moreover, NS rectifies the detrimental impact of feed restriction on performance. Lastly, our study suggests combining NS with feed limitation as a novel approach to improve growth, immunity, and resistance of O. niloticus to edwardsiellosis.

Evaluation of antibacterial activities of Pichia kudriavzevii OQ119615 extract against human pathogenic bacteria, Streptococcus mutans OQ099796 and Streptococcus salivarius OQ102967 - Amal W Danial; Nemmat A Hussein; Mohamed F Edrees; Mohamed A Abdel-Sater; Asmaa M Nasr (South African Journal of Botany, 2025)

Alleviative potential of dietary essential oils against nickel toxicity triggers neurobehavioral abnormalities, biochemical dysfunction, and histopathological alterations in Nile tilapia - Shaimaa A. A. Ahmed; Ali Adel Ali Ahmed; Gehad E. Elshopakey; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Mai Farag Saad; Simon J. Davies; Rowida E. Ibrahim; Asmaa Edrees (Veterinary Research Communications, 2025)

Dietary intervention of propolis and/or turmeric boosted growth, hematology, biochemical profile, and antioxidant-immune responses and their associated gene expression in Nile tilapia (Oreochromis niloticus) challenged with Edwardsiella tarda - Asmaa Edrees; Asmaa S. A. Abdel-Daim; Nema S. Shaban; Olfat Shehata; Rowida E. Ibrahim (Aquaculture International, 2025)
Immunostimulant phytogenic feed additives are given great concern for improving fish health, growth, immune responses, and resistance to diseases. This research investigated the impact of dietary propolis (PRO), turmeric (TUR), and their combination on the growth, hematology, antioxidant-immune responses, and their regulating genes in Nile tilapia ( Oreochromis niloticus ) during Edwardsiella tarda challenge. For 8 weeks, a total number of 320 fish (20.70 ± 0.14 g) were allocated into four groups at random, each with eight replicates (10 fish each). The first group (1st) was given the basal diet (control) without any supplements. The 2nd, 3rd, and 4th groups were supplemented with 1% PRO, 1% TUR, and the mixture (1%PRO + 1%TUR), respectively. The experimental groups were challenged intraperitoneally with E. tarda at a dose of 0.1 mL (1 × 10 5 CFU) at the termination of the feeding trial, and the fish survival was estimated for an additional 7 days. The results demonstrated that fish-fed diets supplemented with PRO and/or TUR showed higher body weight, condition factor, specific growth rate, feed intake, and feed efficiency utilization than the control group ( P NFκB ) and tumor necrosis factor-alpha ( TNF-α ) expression with up-turning of nuclear factor erythroid 2-related factor 2 ( Nrf2 ) and transforming growth factor-beta ( TGF-β ) expression was noticed in the challenged fish fed on PRO and/or TUR diets compared to the challenged non-fed fish. Noteworthy, dietary PRO and/or TUR improved the fish survival during E. tarda challenge. The mixture of PRO and TUR can be added to Nile tilapia diets to enhance their growth, immune response, and resistance to E. tarda . These outcomes help in the sustainable development of the Nile tilapia culture industry. Graphical Abstract

Corrigendum to “Acrylamide exposure induces growth retardation, neurotoxicity, stress, and immune/antioxidant disruption in Nile tilapia (Oreochromis niloticus): The alleviative effects of Chlorella vulgaris diets” [Fish Shellfish Immunol. 146 (2024) 109411] - Asmaa Edrees; Nema S. Shaban; Nour El-Houda Y. Hassan; Asmaa S.A. Abdel-Daim; Mohamed S. Sobh; Rowida E. Ibrahim (Fish & Shellfish Immunology, 2024)

Acrylamide exposure induces growth retardation, neurotoxicity, stress, and immune/antioxidant disruption in Nile tilapia (Oreochromis niloticus): The alleviative effects of Chlorella vulgaris diets - Asmaa Edrees; Nema S. Shaban; Nour El-Houda Y. Hassan; Asmaa S.A. Abdel-Daim; Mohamed S. Sobh; Rowida E. Ibrahim (Fish & Shellfish Immunology, 2024)

The puzzling etiologies of transient black discoloration in Nile Tilapia (Oreochromis niloticus) intensively cultured under RAS system - Alaa Eldin Eissa; Marwa M. Attia; Rabia A. El Zlitne; Ayad A. Magdy; Asmaa Edrees; Mahmoud S. Sharaf; Abeer E. Mahmoud; Awad A. Abdelbaky; Rehab R. Abd ElMaged; Elshaimaa Ismael; Rehab A. Qorany; Doaa F. El Moghazi; et al. (Aquaculture International, 2024)
The aim of this study is to identify the hidden etiologies of the black chromo-shifting transient phenomenon affecting Nile tilapia, Oreochromis niloticus , farmed in RAS-controlled ponds together with the assessment of the immunological reaction against the chronic irritating effects of the invasive agent. A total of 100 Nile Tilapia were collected from a private farm at Kafrelsheikh Province, located on the northern side of the Egyptian Nile Delta. The clinical history of the affected fish farm showed an unknown chromo-shifting phenomenon where tilapias were exhibiting severe black skin coloration, which gradually disappeared after removal from the tank’s water. A comprehensive gross examination of the collected fish; including parasitological examination of skin and gill scraps, was performed. Blood biochemical testing was performed on the infested blackish O. niloticus and control non-infested fish. The current study showed that the monogenean parasite, Gyrodactylus cichlidarum , was the abundant parasite detected in the infested fish leading to abnormal black discoloration of skin and disruption of the immune system represented by significant increase of cortisol levels, lysozyme activity and different liver enzymes compared to the control. Treatment trials have been applied with moderate degrees of success, where the monogenean count was sharply decreased, and the normal skin color was remarkably restored, at the end of day 14 post-treatment. A triple treatment plan was initiated through 7 days’ application of 0.7 g/m 3 copper sulfates pentahydrate preceded by 1.5 ml/m 3 hydrogen peroxide 40% solution for the same period. One day after the end of the initial treatment, a maintenance dosage of 0.095 ml/m 3 of glutaraldehyde (15%)/quaternary ammonium compounds (QACs) mixture was administered for 3 days. As a supportive/immune-stimulant regimen, a weekly dosage of vitamin C (0.45 g g/m 3 ) and Saccharomyces cerevisiae (0.45 g/m 3 ) was added into the tank’s water to improve the general fish health.

Prevalence and associated risk factors of cannabinoid abuse among Egyptian university students: a cross-sectional study - Yahya M. Naguib; Huda A. Sherif; Amr T. Elbalshy; Eslam A. Edrees; Ahmed E. Sabry; Asmaa F. Sharif; Samar H. A. Aloshari; Zeinab A. Kasemy (Environmental Science and Pollution Research, 2021)